Integrasi Nilai Hukum Islam dalam Transparansi dan Keadilan Pemilu: Telaah Pasal 304 UU Pemilu 2017 - Furqon, Ahmad Fauzi; Rahmah, Nur; Irwansyah, Irwansyah; Hayatulloh, Imam (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2024)
This research discusses the analysis of Article 304 Paragraph 1 of Law Number 7 of 2017 concerning General Elections, using an Islamic Law perspective. This article regulates the formation and authority of the institution tasked with organizing elections, namely the KPU (General Election Commission), in order to guarantee a fair, free and transparent democratic process. In the context of siyasah fiqh, this research assesses whether the implementation of these provisions is in line with the principles of government in Islam which emphasize deliberation, justice and the benefit of the people. This research found that although Article 304 Paragraph 1 of the 2017 Election Law aims to increase transparency and fairness in elections, there are challenges in its implementation, especially related to the principles of siyasah fiqh, such as the importance of equal justice for all elements of society and effective supervision of institutions. election organizer. From an Islamic Law perspective, the principles contained in Article 304 are acceptable, as long as the monitoring, accountability and transparency mechanisms are implemented responsibly by the KPU. Overall, the application of the provisions in this Article must be seen within the framework of Islamic values which emphasize the importance of people's participation, trust and social justice. It is hoped that this research can contribute ideas in developing an electoral system that is not only based on positive legal norms, but is also in line with the values of Islamic law which can strengthen the legitimacy and sustainability of the democratic system in Indonesia. [Penelitian ini membahas tentang analisis Pasal 304 Ayat 1 Undang-Undang Nomor 7 Tahun 2017 tentang Pemilihan Umum, dengan menggunakan perspektif Hukum Islam. Pasal tersebut mengatur mengenai pembentukan dan wewenang lembaga yang bertugas menyelenggarakan Pemilu, yaitu KPU (Komisi Pemilihan Umum), dalam rangka menjamin proses demokrasi yang adil, bebas, dan transparan. Dalam konteks fiqih siyasah, penelitian ini menilai apakah pelaksanaan ketentuan tersebut sejalan dengan prinsip-prinsip pemerintahan dalam Islam yang menekankan pada musyawarah, keadilan, dan kemaslahatan umat. Penelitian ini menemukan bahwa meskipun Pasal 304 Ayat 1 UU Pemilu 2017 bertujuan untuk meningkatkan transparansi dan keadilan dalam Pemilu, terdapat tantangan dalam penerapannya, terutama terkait dengan prinsip-prinsip fiqih siyasah, seperti pentingnya keadilan yang merata bagi seluruh elemen masyarakat dan pengawasan yang efektif terhadap lembaga penyelenggara Pemilu. Dari perspektif Hukum Islam, prinsip-prinsip yang terkandung dalam Pasal 304 ini dapat diterima, asalkan mekanisme pengawasan, akuntabilitas, dan transparansi dijalankan dengan penuh tanggung jawab oleh KPU. Secara keseluruhan, penerapan ketentuan dalam Pasal ini harus dilihat dalam kerangka nilai-nilai Islam yang menekankan pentingnya partisipasi rakyat, amanah, dan keadilan sosial. Penelitian ini diharapkan dapat memberikan kontribusi pemikiran dalam pengembangan sistem pemilu yang tidak hanya berlandaskan pada norma hukum positif, tetapi juga sejalan dengan nilai-nilai Hukum Islam yang dapat memperkuat legitimasi dan keberlanjutan sistem demokrasi di Indonesia].